Effect of Alumina Addition on the Microstructure and Mechanical Properties of Metal Inert Gas Welded Low Carbon Steel. Issue 3 (3rd July 2017) - Sathish, S.; Geetha, M.
ABSTRACT: In this study, influence of alumina addition on weld appearance, microstructure and mechanical properties of metal inert gas (MIG) welded low carbon mild steel were emphatically investigated. Experimental results show that all the joints were smooth with free of cracks. Microstructures of MIG and laser remelted joints show the presence of columnar and equiaxed dendrites. Furthermore, superior microhardness of MIG welded joint over alumina added and laser remelted joints is ascribed to the presence of columnar dendrites. Fractography of the tensile tested alumina added joint exhibited a mixed mode of ductile and brittle characteristics and this is attributed to the presence of acicular ferrites and bainite in the microstructure. GRAPHICAL ABSTRACT: